Memahami Kultur Keagamaan Di Tasikmalaya Dalam Perspektif Sejarah - Hambaliana, Dandie; Nurcahya, Yan; Oksa Putra, M Zikril; Thariq Syah, M Kautsar (UPT Publikasi Ilmiah, 2024)
Tasikmalaya has a very extraordinary culture of diversity where almost all of the people are Muslim, this is evidenced by the large number of pesantren in Tasikmaaya, which in the course of its history has contributed enough to the social life of the community and the nation, as we see in the history of the pesantren founded by KH. Zaenal Mustofa who was so hard against the Dutch and Japanese colonization, in this paper will present information about the socio-cultural history of religion in Tasikmalaya. This paper discusses the role of Islamic organizations such as Masyumi and Darul Islam (DI) in the political and social context of Tasikmalaya in the 1950s. The type of research used is qualitative with a library research method through the stages of observation, library documentation, and interviews. It also explains the contradictions between economic development and security conditions in the region. Through this analysis, the complexity of Tasikmalaya's religious culture and its impact on society and the state can be understood.